ALLERGIC EYE DISEASES IN CHILDREN. MODERN VIEW ON PATHOGENESIS AND TREATMENT - E. Y. Markova; E. G. Polunina; E. E. Ioileva (Oftalʹmologiâ)
The prevalence off allergic diseases has  been  significantly increased among  adults  and children during last 30-40 years. International study has  shown  that  the  frequency  of atopy  in developed  countries, including Russia,   is higher  than  in developing.  Often atopic dermatitis, started in infancy, can develop into an “allergic march”  — food allergy, followed by the formation of allergic rhinitis, allergic conjunctivitis and  other  allergic diseases. The problem  of prophylaxis and  treatment of allergic pathology  becomes actual  for these reasons. An opinion according some  preventive  measures has  changed in recent. It was  noted  that  in families  with many children, where  children  were  often  sick  with respiratory infections,  the  incidence  of allergic  diseases was  lower  than  among  rarely sick children.  It is explained by the  “hygienic theory” — insufficient “training” of the  Th1 response in rarely sick children.  Allergic diseases, which are  based on IgE-mediated inflammation,  have a common  pathogenetic nature and,  consequently, general  principles of therapy, in which, as  is well known,  antihistamines take  a significant  place.  This is cased by the  mandatory involvement of histamine  in the mechanism of development of the main symptoms of allergic diseases. Current  capabilities  of local ophthalmologic  antiallergic therapy includes medicines  with multiple action mechanisms, such as mast cell stabilizers, antihistamines, combined  agents, steroids and nonsteroidal anti-inflammatory effects. The latest generation antihistamine drug — olopatadine hydrochloride  0.2% is a new form of the molecule of olopatadine, which is intended  to increase the duration  of the action.  The article considers the main modern directions in prevention  and treatment of allergic diseases, including allergic eye diseases, which are  a manifestation of the underlying disease and have a common  pathogenetic nature to all atopic diseases, based on the IgE-mediated inflammation reaction.